2020
DOI: 10.1039/d0cc05514j
|View full text |Cite
|
Sign up to set email alerts
|

Zinc ferrite-based p–n homojunction with multi-effect for efficient photoelectrochemical water splitting

Abstract: The novel one-dimensional core-shell zinc ferrite (ZnFe2O4) p-n homojunction is prepared by a facile two-step hydrothermal method. Core-shell homojunction is constructed by decorating p-type Ni-ZnFe2O4 (shell) on n-type ZnFe2O4 (core)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…With the addition of Zn 2+ and/or Al 3+ the ratio of satellite peak increased, the content of Fe 3+ increased, it may be accompanied by the generation of ZnFe 2 O 4 . 23,24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of Zn 2+ and/or Al 3+ the ratio of satellite peak increased, the content of Fe 3+ increased, it may be accompanied by the generation of ZnFe 2 O 4 . 23,24 …”
Section: Resultsmentioning
confidence: 99%
“…With the addition of Zn 2+ and/or Al 3+ the ratio of satellite peak increased, the content of Fe 3+ increased, it may be accompanied by the generation of ZnFe 2 O 4 . 23,24 The Mn2p spectra consisted of Mn2p 3/2 ($641 eV) and Mn2p 1/2 ($652 eV) with an additional satellite peak at approximate 646-647 eV, which conrmed the presence of Mn 2+ state (MnO or MnFe 2 O 4 ) in the oxide lms. 25 According to the XPS survey scan of each specimen in Table 6, aer Zn 2+ added into solution, the percentage of Mn decreased from 17% to 12%, which may be due to the replacement of Mn 2+ (MnFe 2 O 4 ) by Zn 2+ (ZnFe 2 O 4 ).…”
Section: Xps Analysismentioning
confidence: 99%
“…68 Moreover, the built-in potential and electron driving force can be modulated by tuning the conduction band and the Fermi level states by doping of ZnO. 14,69 Yang et al have reported the synthesis of a nitrogen-doped ZnO nanowire photoanode by a hydrothermal method and an annealing process in ammonia atmosphere, achieving an order of magnitude enhancement in photocurrent density with an STH efficiency of 0.15% at +0.5 V (vs Ag/AgCl). 46 Pan et al have calculated the band structure, optical absorption, and thermodynamic stability of several n−p pair (including Sc + N, Ti + C, Sc + C, Ti + N, V + C, V + N, Cr + C, and Cr + N)codoped ZnO, demonstrating that these dual-element codoped ZnO are promising candidates for photoanodes in PEC-WS systems because of their appropriate band gap value and energy level positions, reduced carrier recombination sites, improved photons absorption, and strong stability.…”
Section: Morphology and Architecture Manipulationmentioning
confidence: 99%
“…11−13 It is well recognized that PEC-WS provides a hopeful strategy to convert the discontinuous solar energy into reproducible and storable hydrogen fuel energy. 14,15 Specifically, PEC-WS devices can split water into hydrogen and oxygen under sunlight irradiation by generating electrons and holes to drive the water splitting reaction, and thus generation of hydrogen by PEC-WS shows promising potential in the current renewable clean energy scenario. 16,17 In a typical PEC-WS configuration, semiconductor materials can absorb incident photons to generate carriers, and then the photoinduced carriers can be separated and transported to the interface of the semiconductor and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5–14 ] As a key component in quality PEC‐WS configuration, the photoanode should meet the following requirements: i) high light response intensity and wide light absorption region; ii) rapid carrier separation, extraction, and transport process; iii) the surface reaction kinetics. [ 15–17 ] Importantly, the solar to hydrogen conversion efficiency (STH) of PEC‐WS system is also determined by the above‐mentioned factors. [ 18–21 ] Therefore, developing an efficient photoanode is crucial for achieving superior PEC‐WS apparatus with high STH efficiency.…”
Section: Introductionmentioning
confidence: 99%